2022
DOI: 10.1111/imj.15677
|View full text |Cite
|
Sign up to set email alerts
|

Proposed empiric antibiotic therapy for prosthetic joint infections: an analysis of the Prosthetic Joint Infection in Australia and New Zealand, Observational (PIANO) cohort

Abstract: Empiric antibiotic therapy in suspected prosthetic joint infection should cover likely pathogens while avoiding overly broad‐spectrum antibiotics. We analysed individual patient data from a large prospective cohort study (Prosthetic Joint Infection in Australia and New Zealand, Observational (PIANO)) and found that causative organisms vary with the presentation type, with early post‐operative infections more likely to be polymicrobial (41%) compared with late acute infections (10%). We thus propose empirical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…PJIs can be classified as early (within 30–90 days following joint replacement, usually due to peri‐operative acquisition of pathogenic bacteria), chronic (months to years post‐operatively with low grade symptoms), and late acute (months to years post‐operatively with an acute onset of symptoms in a previously well functioning joint, usually caused by bacterial seeding during blood stream infections). This classification is important because of differences in underlying bacterial aetiology, 6 diagnostic criteria, empirical antibiotic choices, 7 surgical strategy, and outcome 8 …”
Section: Definition and Classificationmentioning
confidence: 99%
“…PJIs can be classified as early (within 30–90 days following joint replacement, usually due to peri‐operative acquisition of pathogenic bacteria), chronic (months to years post‐operatively with low grade symptoms), and late acute (months to years post‐operatively with an acute onset of symptoms in a previously well functioning joint, usually caused by bacterial seeding during blood stream infections). This classification is important because of differences in underlying bacterial aetiology, 6 diagnostic criteria, empirical antibiotic choices, 7 surgical strategy, and outcome 8 …”
Section: Definition and Classificationmentioning
confidence: 99%
“…In the case of late acute PJI, cefazolin is also recommended. If a chronic non-septic form occurs, antibiotic therapy should be suspended until the culture results are obtained [ 133 ]. A study conducted at the Orthopedic Surgery Center in Zhengzhou, China from January 2012 to December 2018 showed that the empirical antibiotic therapy should include a combination of vancomycin with either cephalosporin, levofloxacin, or clindamycin.…”
Section: Antibiotic Therapymentioning
confidence: 99%